Cochlear tuning estimates from level ratio functions of distortion product otoacoustic emissions. (2nd November 2021) - Wilson, Uzma Shaheen; Browning-Kamins, Jenna; Durante, Alessandra Spada; Boothalingam, Sriram; Moleti, Arturo; Sisto, Renata; Dhar, Sumitrajit
Abstract: Objective: Distortion product otoacoustic emission (DPOAE) levels plotted as a function of stimulus frequency ratio demonstrate a bandpass shape. This bandpass shape is narrower at higher frequencies compared to lower frequencies and thus has been thought to be related to cochlear mechanical tuning. Design: However, the frequency- and level-dependence of these functions above 8 kHz is largely unknown. Furthermore, how tuning estimates from these functions are related to behavioural tuning is not fully understood. Study Sample: From experiment 1, we report DPOAE level ratio functions (LRF) from seven normal-hearing, young-adults for f2 = 0.75–16 kHz and two stimulus levels of 62/52 and 52/37 dB FPL. We found that LRFs became narrower as a function of increasing frequency and decreasing level. Results: Tuning estimates from these functions increased as expected from 1-8 kHz. In experiment 2, we compared tuning estimates from DPOAE LRF to behavioural tuning in 24 normal-hearing, young adults for 1 and 4 kHz and found that behavioural tuning generally predicted DPOAE LRF estimated tuning. Conclusions: Our findings suggest that DPOAE LRFs generally reflect the tuning profile consistent with basilar membrane, neural, and behavioural tuning. However, further investigations are warranted to fully determine the use of DPOAE LRF as a clinical measure of cochlear tuning.